Obrót nieruchomościami rolnymi w Polsce z udziałem cudzoziemców - stan i perspektywy - Klusek, Tomasz (Agricultural Property Sales for Foreigners in Poland - Situation and Outlook, 2005)
The issue of property purchasing by foreigners has been one of hot topics due to a discussion which particularly concerns agricultural properties.The study concerns the scope of agricultural property sales for foreign natural persons and businessmen as well as future prospects of this phenomenon in respect of new legal framework.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 437-442